10.1016/s1541-9800(09)70194-2 (CrossRef Listing of Deleted DOIs, 2000)
INTRODUCTION: Trauma is a risk factor for mental health problems. Pathological dissociation is often theorized as a response to trauma, yet it remains a controversial topic. AIM: The present study is one of the very few to examine trauma and dissociation in a representative general population sample and is the first of its kind in the Chinese context. We examined the prevalence of pathological dissociation and its association with trauma, potential iatrogenic effects, and functional impairment. METHODS: A random sample of community Hong Kong Chinese adults (N = 945) completed validated measures of trauma exposure, dissociative symptoms, depressive symptoms, and functional impairment. RESULTS: In this sample, 33.3% endorsed at least one potentially traumatic event; 16.5% exhibited clinically significant pathological dissociation, of whom only 14.8% had ever sought professional mental health services. Childhood betrayal and non-betrayal trauma and adulthood betrayal trauma were significantly associated with dissociative symptoms, while adulthood non-betrayal trauma was not. Dissociative symptoms were the strongest predictor of functional impairment (β = 0.443, p < 0.001), even stronger than depressive symptoms (β = 0.384, p < 0.001). DISCUSSION: This study highlights the public health and clinical importance of recognizing dissociation, which is comparably prevalent to depression and even more strongly linked to functional impairment. Our results support the trauma model in general, but do not support the betrayal trauma theory or the iatrogenic model. IMPLICATIONS: Dissociative symptoms are prevalent and clinically significant in the community. Nurses should be trained to identify and support people affected by pathological dissociation.